Choix résidentiel et gentrification dans une ville moyenne - Patrick Rérat (Cybergeo, 2012)
After three decades of demographic decline, Swiss cities have registered a new period of growth since 2000. One of the explanations of this trend reversal is the construction in the frame of urban regeneration projects of dwellings addressed to the middle to high classes (« new-build gentrification »). This paper focuses on the characteristics of people living in recently built dwellings in Neuchatel, a 33 000 inhabitant city. On the basis of a questionnaire survey, it addresses the characteristics of these households (profiles, trajectories, motivations). Results show a diversification of the middle to high classes whose residential aspirations are less and less oriented towards the detached house in suburbs. The results also generally give more information on gentrification processes in small and medium cities.